Consensus on the management of platinum-sensitive high-grade serous epithelial ovarian cancer in Lebanon - Reem Abdallah; David Atallah; Nizar Bitar; Georges Chahine; Hady Ghanem; Marwan Ghosn; Joseph Kattan; Fadi Nasr; Joseph Makdessi; Ali Shamseddine (Elsevier, 2023)
Ovarian cancer is the most lethal gynecologic cancer. The high grade serous epithelial (HGSE) subtype is the most aggressive and it often presents at advanced stages, while screening programs have not proven beneficial. Management of the advanced stages (FIGO III and IV), which constitute the majority of diagnoses, usually consists of platinum-based chemotherapy and cytoreductive surgery (primary or interval) followed by maintenance therapy. Currently, the standard-of-care for advanced newly diagnosed HGSE ovarian cancer, as per international medical societies, starts with upfront cytoreductive surgery, followed by platinum-based chemotherapy (mostly carboplatin and paclitaxel) and/or anti-angiogenic agent bevacizumab, then maintenance therapy with a poly(ADP-ribose) polymerase (PARP) inhibitor with/without/or bevacizumab (continued). PARP inhibitor use depends on the patient's genetic signature, mainly the breast cancer gene (BRCA) mutation and the homologous recombination deficiency (HRD) status. Therefore, genetic testing is recommended at diagnosis to inform treatment and prognosis.In line with the evolving standard-of-care for ovarian cancer, a panel of experts in treating advanced ovarian cancer convened to lay down practical recommendations on the management of advanced ovarian cancer in Lebanon; since the currently applicable guidelines by the Lebanese Ministry of Public Health for cancer treatment have not been updated yet to reflect the treatment paradigm shift brought upon by the development and approval of PARP inhibitors. The current work reviews the leading clinical trials on PARP inhibitors (as maintenance for newly diagnosed advanced and platinum-sensitive relapsed ovarian cancer), presents international recommendations, and proposes treatment algorithms for optimal local practice.